Nutritional awareness among pregnant women in Latvia - Kolosova, Marija; Miskova, Med. Anna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Women's eating habits affect not only the course of pregnancy but also the later life's metabolic health of their off springs. In 2016 Latvian guidelines on healthy nutrition during preconception period, pregnancy and lactation were published. The aim of this study was to analyze the level of nutritional awareness among pregnant women in Latvia. Methods: A descriptive cross-sectional study was carried out in Riga Maternity Hospital. 110 pregnant women receiving antenatal care participated in the survey. Results: 64.5% of respondents received recommendations on proper nutrition from health care professionals during pregnancy, whereas only 20.9% were informed in the preconception period. 68.7% of participants, who received information about the principles of healthy nutrition, considered them to be sufficient. The majority of women got the recommendations from gynecologists-obstetricians- 4.9%. 39.1% of women used non-evidence-based sources when searching for the information about healthy nutrition. 34.5% of all pregnant women had at least one health or social risk factor, which required individualized diet planning, however, 26.3% of them did not receive any recommendations at all. 28.7% of respondents started pregnancy with abnormal Body Mass Index (BMI). Conclusions: Women should be advised to make diet corrections before pregnancy, therefore more consultations in preconception period are needed. Additional educational sources providing information about healthy nutrition should be considered.